A MATCHING ANALYSIS OF ESG INFORMATION DISCLOSED IN SUSTAINABILITY AND FINANCIAL REPORTS OF HIGHPOLLUTING COMPANIES FROM THE OIL INDUSTRY - Réka Melinda TÖRÖK (Annals of the University of Oradea: Economic Science)
The financial world has a prominent role to play in the global economic action plan. The financial sector together with stock exchanges around the world promotes sustainability, environmental (Environmental), social (Social), and governance (Governance), i.e. ESG factors, and the importance of incorporating them into investment decision-making and capital allocation to sustainable assets. The purpose of the undertaken study is to observe and analyze the extent to which the commitments made through the Sustainability Reports materialize and have financial quantifications in the Annual Financial Reports published by three large companies in the oil sector. The OMV Petrom ESG disclosure score determined based on the information in the sustainability report is very close to the ESG estimates score calculated from the financial report, which allows us to consider that the commitments in the sustainability report have been achieved.